Attitude of Mathematics Teachers Towards the Use of Activity Based and Guided Discovery Strategies in Improving Students Understanding of Geometric Concepts - B, Shiaki O.; Y, Bernard A.; H, Takwa; P, Caleb (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
The study aims to examine attitude of mathematics teachers towards the use of Activity Based teaching strategy and Guided discovery teaching strategy in improving students’ understanding of Geometric concepts. The study used survey design with half of the students (50) were subjected to Activity based teaching strategy and the remaining half were subjected to guided discovery teaching strategy (50) making a sample size of 100 students for the research study. A total of 26 mathematics teachers were used for the study, where 13 teachers were those who employed guided discovery teaching strategy and the remaining 13 were subjected to answer questions based on their attitude towards using activity-based teaching strategy to improve students understanding of geometric concepts known as Mathematics Teachers Attitude Test (MTAT). The attitudinal scale was determine using Likert 4 point scale for SA (strongly Agree), A (Agree), D (Disagree) and SD (Strongly Disagree) respectively. However, the 100 students were split into two groups and questions in selected areas of geometry were formulated by the researchers also known as Students Geometric Achievement Test (SGAT). The researchers used simple random sampling to select the 100 students based on the use of guided discovery teaching strategy and activity based teaching strategy in Zing LGA, Taraba State, Nigeria by their Mathematics Teachers. The method used for data analysis is mean scores, standard deviation and t-test distribution. Results of the study revealed that mathematics teachers of the study area have interest in the use of Activity based teaching strategy and Guided discovery teaching strategy to improve students understanding of geometric concepts. Teachers believe in this study that students do not feel boring when guided discovery teaching strategy is used in teaching geometric concepts to them. At 5% level of significance it was revealed further that, there is no significant difference in the Attitude of mathematics teachers on the use of Activity based teaching and guided discovery teaching strategies to improve students understanding of geometric concepts. It was recommended in this study that teachers should endeavor to employ the two selected teaching strategies in other to improve students understanding of geometric concepts in Zing local government Area.